2019
DOI: 10.3201/eid2508.190089
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Dengue Surveillance and Research, Puerto Rico, 1899–2013

Abstract: Dengue was first reported in Puerto Rico in 1899 and sporadically thereafter. Following outbreaks in 1963 and 1969, the Centers for Disease Control and Prevention has worked closely with the Puerto Rico Department of Health to monitor and reduce the public health burden of dengue. During that time, evolving epidemiologic scenarios have provided opportunities to establish, improve, and expand disease surveillance and interventional research projects. These initiatives have enriched the tools available to the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
34

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 38 publications
(50 reference statements)
0
20
0
34
Order By: Relevance
“…In summary, Puerto Rico experienced a large ZIKV outbreak in 2016 in which~1% of residents were reported to public health authorities and had evidence of ZIKV infection. Fine scale analysis of the epidemiologic and spatiotemporal characteristics demonstrated that, in contrast to prior epidemics of dengue and chikungunya that began in the San Juan metropolitan area [11,12], ZIKV transmission was first detected in eastern Puerto Rico in late 2015 and rapidly spread to all municipalities of the island during 2016. As expected, geography, climate, community characteristics, and human factors all influenced the observed trends of ZIKV disease.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, Puerto Rico experienced a large ZIKV outbreak in 2016 in which~1% of residents were reported to public health authorities and had evidence of ZIKV infection. Fine scale analysis of the epidemiologic and spatiotemporal characteristics demonstrated that, in contrast to prior epidemics of dengue and chikungunya that began in the San Juan metropolitan area [11,12], ZIKV transmission was first detected in eastern Puerto Rico in late 2015 and rapidly spread to all municipalities of the island during 2016. As expected, geography, climate, community characteristics, and human factors all influenced the observed trends of ZIKV disease.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Surveillance for dengue has operated in the Caribbean U.S. territory of Puerto Rico since the 1960s [11] and was expanded to include chikungunya in 2014 [12]. Following detection of ZIKV transmission in the Americas in 2015 [13], Puerto Rico Department of Health (PRDH) initiated laboratory-based surveillance for ZIKV disease through the existing arboviral diseases surveillance system [14].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, during the study period, DENV-1 and DENV-4 were the main circulating serotypes in Puerto Rico. 12 Although none of the study participants was clinically diagnosed with a Zika virus infection, Y3 coincided with a Zika virus epidemic in Puerto Rico in 2016. 13 Cross-reactivity between antibodies to Zika virus and DENV has previously been reported 14,15 and is likely due to substantial similarity in the sequence type of surface glycoprotein E. 16 Based on these results, the 1 μg+AS03 B formulation administered according to different dose schedules was assessed in a subsequent clinical trial (NCT02421367; L. Lin et al, unpublished data).…”
Section: Discussionmentioning
confidence: 96%
“…The outbreak tells us early detection and diagnosis of cases is key to controlling the spread of an epidemic; timely and effective mosquito control in the early stage of epidemic is another key measure. Thus, during the epidemic period of dengue, more proactive countermeasures must be taken such as intensifying surveillance for dengue cases, virus, and the vector Aedes ; strengthening the cooperation with customs and tourism departments to yield close partnerships that will be integral components of successful public health initiatives to combat dengue ( 6 ); and improving the capacity of medical institutions to promptly detect and diagnosis dengue cases. Through early warning and coordination, we can detect the spread of dengue-fever.…”
Section: Discussionmentioning
confidence: 99%
“…The prompt diagnosis and management of cases are key measures in controlling the spread of the outbreak, and the clinical manifestations of dengue were closely related to the diagnosis, so that correct understanding and analysis of clinical symptoms, combined with investigations of the epidemiological history, are helpful to improve the efficiency of diagnosis and treatment (4)(5). By investigating and analyzing the median onset-to-diagnosis interval in this outbreak, we found that enhancing the ability of medical faculty to quickly detect and diagnose dengue cases is highly needed.…”
Section: Discussionmentioning
confidence: 99%